Powdery Mildew on Carob First Recorded in the Green Mountain Area of Libya - Almijbari, Salih Husayn Muhamad (Al-Mukhtar Journal of Sciences, 1992)
Surveys and primay investigation were conducted to investigate powdery mildew disease on CAROB (Ceratonia siligua. L) in seven Regions: Alwaseitah, Al-Haniah, Al-Hamamah, Omar Al-Mukhtar, Massah, AlGhareika, and Wadi. Alkuff in the Green Mountain area of Libya. The causal organism was identifies as Oidium Ceratonia based on the presence of the conidial stage which was ob. served and isolated from infected leaf samples. The Powdery Mildew disease was Found in all studied regions at different levels of infection. The highest level of infection 80% was found in wadi. Alkuff. the second level 60% at AlWaseitah and Al-Haniah, while AlHamamah, Omar Al-Mukhtar, Massah and Al-Ghareika all showed infection levels of 40.